Pre- and postsynaptic N-methyl-D-aspartate receptors are required for sequential printing of fear memory engrams - Ilaria Bertocchi; Florbela Rocha-Almeida; María Teresa Romero-Barragán; Marco Cambiaghi; Alejandro Carretero-Guillén; Paolo Botta; Godwin K. Dogbevia; Mario Treviño; Paolo Mele; Alessandra Oberto; Matthew E. Larkum; Agnes Gruart; et al. (iScience, 2023)
Summary: The organization of fear memory involves the participation of multiple brain regions. However, it is largely unknown how fear memory is formed, which circuit pathways are used for “printing” memory engrams across brain regions, and the role of identified brain circuits in memory retrieval. With advanced genetic methods, we combinatorially blocked presynaptic output and manipulated N-methyl-D-aspartate receptor (NMDAR) in the basolateral amygdala (BLA) and medial prefrontal cortex (mPFC) before and after cued fear conditioning. Further, we tagged fear-activated neurons during associative learning for optogenetic memory recall. We found that presynaptic mPFC and postsynaptic BLA NMDARs are required for fear memory formation, but not expression. Our results provide strong evidence that NMDAR-dependent synaptic plasticity drives multi-trace systems consolidation for the sequential printing of fear memory engrams from BLA to mPFC and, subsequently, to the other regions, for flexible memory retrieval.